Synthesis and Characterization of Activated Carbon from Jackfruit Banana (Musa paradisiaca L.) Leaves as Supercapacitor Electrode Material - Satria Ulia Uliana; Bidayatul Armynah; Emar Mokiman Kala’Tagari (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2026)
A study was conducted to determine the maximum carbonization temperature for producing activated carbon derived from banana leaves (Musa paradisiaca L.) as electrode material for supercapacitors with KOH activation. Activated carbon was prepared using a chemical activation method with 0.5 M KOH at carbonization temperatures of 750, 800, and 850 °C under a CO₂ atmosphere. Thermogravimetric (TG) and Derivative Thermogravimetric (DTG) analyses revealed the highest thermal degradation rate at 313.3 °C, indicating the temperature range with the most rapid mass loss. Density analysis showed that the density of activated carbon decreased with increasing carbonization temperature. Fourier Transform Infrared (FTIR) characterization confirmed the presence of carbon bonds, while X-Ray Diffraction (XRD) patterns indicated a mixed amorphous–semi-crystalline structure. Scanning Electron Microscopy (SEM) analysis revealed a surface morphology with more uniformly distributed and open pores, indicating enhanced pore development with increasing carbonization temperature. Energy Dispersive X-ray Spectroscopy (EDS) confirmed the dominance of potassium, accounting for 73.77 wt% and 49.80 at%. Electrochemical evaluation showed that the specific capacitance exhibited only slight variations across the tested carbonization temperatures, with the highest value of 209 F/g obtained at 850 °C. These results indicate that 850 °C is the maximum carbonization temperature to produce high-performance activated carbon from banana leaves, reinforcing its potential as a sustainable material for supercapacitor applications.